Scourge of Ages: African Union’s Peace and Security Council (PSC) Interventions in Somalia and the Free Reign of Violence in Africa - BAMIDELE , Oluwaseun; IDOWU, Olusegun Oladele (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2024)
For the draftsmen and composers of the African Union (AU), the organ of Peace and Security Council (PSC) is not only a clone of the Security Council of the United Nations; it is intended to give aggregate security and early-cautioning course of action against Africa's unlimited clashes and to encourage auspicious and proficient reaction. Also, the Constitutive Act and the Protocol on the PSC accommodate more vigorous engagement and significantly more noteworthy extension in examples of both between and intra-state clashes. Be that as it may, the intercessions of the PSC in some of Africa's auditoriums of contention have brought up central issues on how the organ plays out its triangular parts of contention anticipation, administration, and determination. With a unique spotlight on the Horn of Africa - the most unstable and seemingly a standout amongst the most hazardous districts on the planet, the paper expects to evaluate the difficulties confronting PSC mediation instruments, particularly the parts of the African Standby Force and its activities. The paper contends that the PSC must move past negligible talk of plan setting to more 'powerful or aggressive' engagement by fortifying its tasks. It at last backers’ proactive strategy choices on how its parts could be upgraded in the district.